2015
DOI: 10.1177/0300060515591063
|View full text |Cite
|
Sign up to set email alerts
|

Association between red blood cell distribution width and disease activity in patients with Behçet’s disease

Abstract: Objectives: To examine associations between red blood cell distribution width (RDW) and organ involvement and disease activity in patients with Behçet's disease. Methods: Haematological and inflammatory parameters including RDW, high-sensitivity C-reactive protein (hsCRP) and erythrocyte sedimentation rate (ESR) were examined in patients with Behçet's disease and in healthy controls. Patients were divided into those with active or inactive disease. Results: Data from 236 patients with Behçet's disease (77 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
3
18
1
2
Order By: Relevance
“…Behçet's disease is chronic inflammatory disease. Therefore there were some studies in which high CRP and ESR levels were calculated [24]. In this study, ESR and albumin levels were high in BD group.…”
Section: Discussionmentioning
confidence: 70%
“…Behçet's disease is chronic inflammatory disease. Therefore there were some studies in which high CRP and ESR levels were calculated [24]. In this study, ESR and albumin levels were high in BD group.…”
Section: Discussionmentioning
confidence: 70%
“…[21] Several studies have been published regarding the relationship between RDW and inflammatory disease. RDW can be used as a novel potential parameter to evaluate disease activity in inflammatory bowel disease, Behçet disease, and systemic lupus erythematosus, [11,22,23] and RDW was correlated with inflammatory parameters such as CRP, ESR, tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6). [2325] Oxidative stress, which might be effective in damaging erythrocyte membrane, perturbing normal energy metabolism in erythrocytes, and reducing erythrocyte life span, [26] was also reported to be associated with RDW.…”
Section: Discussionmentioning
confidence: 99%
“…1 Division of Rheumatology, Allergy and Immunology, Taoyuan City, Taiwan, Republic of China; 2 Center fo big data analytics and statistics, Taoyuan City, Taiwan, Republic of China Background: Previous studies have reported an increased risk of multiple comorbidities in people with RA therefore it is necessary to systematically quantify the comorbidity burden of these patients. [1] The comorbidity index is a tool developed under this concept and has multiple clinical and research uses. Objectives: We compared four comorbidity indexes and mortality rate in patients with rheumatoid arthritis in Taiwan (Charlson Comorbidity Index (CCI), Elixhauser Comorbidity Index (ECI), Mutimorbidity index (MMI), Rheumatic Disease Comorbidity Index (RDCI)) Methods: All patients with rheumatoid arthritis diagnosed during 1998-2008 in Taiwan were identified using the Taiwan National Health Insurance Database and followed up to 31 Dec 2013.…”
Section: Ab0259mentioning
confidence: 99%